Gender-Specific Combination HIV Prevention for Youth in High-Burden Settings: The MP3 Youth Observational Pilot Study Protocol. - Buttolph, Jasmine; Inwani, Irene; Agot, Kawango; Cleland, Charles M; Cherutich, Peter; Kiarie, James N; Osoti, Alfred; Celum, Connie L; Baeten, Jared M; Nduati, Ruth; Kinuthia, John; Hallett, Timothy B; et al. (JMIR research protocols, 2017)
Nearly three decades into the epidemic, sub-Saharan Africa (SSA) remains the region most heavily affected by human immunodeficiency virus (HIV), with nearly 70% of the 34 million people living with HIV globally residing in the region. In SSA, female and male youth (15 to 24 years) are at a disproportionately high risk of HIV infection compared to adults. As such, there is a need to target HIV prevention strategies to youth and to tailor them to a gender-specific context. This protocol describes the process for the multi-staged approach in the design of the MP3 Youth pilot study, a gender-specific, combination, HIV prevention intervention for youth in Kenya.